Guest and Insecure: the 1973 crisis and the fate of the Greek Gastarbeiter in West Germany - Maria ADAMOPOULOU (Diacronie. Studi di Storia Contemporanea, 2023)
Crisis has a strong hermeneutical power, a potential to shape collective imaginaries and to provoke panic. In this article, I examine how the debates around the oil crisis of 1973 and the consequent recruitment halt in West Germany were framed in the Greek printed and audiovisual media. The Greek migrant workers are the focus group of this investigation and the questions asked are how the crisis impacted their status in the host country and how this disruption influenced their decision-making regarding settlement and return. The different stakeholders involved in the Greek Gastarbeiter migration, namely politicians, media, trade unions and migrants articulated their hopes, anxieties and critique, shaped and challenged the actual policymaking in the framework of the Cold War and the European enlargement project.